Tenure, Faculty Contracts and Bargaining Conflict - Hum, Derek (Canadian Journal of Higher Education, 2017)
Tenure is sometimes charged as giving faculty lifetime job security, with little accountability and sporadic monitoring of performance. Scholars have traditionally defended tenure as necessary for academic freedom. This paper takes a different approach by examining the academic "employment contract relationship," and explaining how tenure can lead to bargaining conflict. Tenure is costly to the university but extremely valued by the faculty member. The opportunity cost of granting tenure to someone is the lost teaching and research output of younger people who cannot be hired in future. Tenure is necessary because without it, incumbents would never recommend hiring people who might be better than they are, for fear of being replaced. Tenure is also efficient because faculty have better information about incumbents than either university administrators or outside consultants. Tenure is therefore necessary to motivate older faculty to hire the best. With staff budget dollars able to be shifted back or forwards across time periods, tenure secures the truthful revelation of who are the good candidates over all periods, and the university is guaranteed that those who are in the best position to judge (namely, faculty rather than administrators) have every incentive to make the best decisions. It follows, then, that the naive suggestion to get rid of tenure so that older, expensive professors can be fired and replaced with younger, cheaper professors would be disastrous in the long run. A simple model is presented explaining why (a) recent cutbacks in government grants, (b) cost pressures on university budgets, (c) limits to tuition increases, and (d) declining interests in attending a less "excellent" university have all resulted in pressure on tenure. Because there is no previously agreed-to mechanism in place to adjust staff, university administrations and faculty unions are not so much bargaining over an acceptable contract outcome as they are contesting the very rules of the bargaining game. Accordingly, unless tenure is reconsidered, universities may increasingly face bargaining conflict. Tenure could be reformed by making the term of tenure limited but related to rank, and establishing a maximum eligibility period during which a faculty may apply for promotion.